Initial experience using the rigid forceps technique to remove wall‐embedded IVC filters. Issue 3 (6th March 2015) - Avery, Allan; Stephens, Maximilian; Redmond, Kendal; Harper, John
Abstract Introduction Severely tilted and embedded inferior vena cava (IVC) filters remain the most challenging IVC filters to remove. Heavy endothelialisation over the filter hook can prevent engagement with standard snare and cone recovery techniques. The rigid forceps technique offers a way to dissect the endothelial cap and reliably retrieve severely tilted and embedded filters. By developing this technique, failed IVC retrieval rates can be significantly reduced and the optimum safety profile offered by temporary filters can be achieved. We present our initial experience with the rigid forceps technique described by Stavropoulos et al. for removing wall‐embedded IVC filters. Methods We retrospectively reviewed the medical imaging and patient records of all patients who underwent a rigid forceps filter removal over a 22‐month period across two tertiary referral institutions. Results The rigid forceps technique had a success rate of 85% (11/13) for IVC filter removals. All filters in the series showed evidence of filter tilt and embedding of the filter hook into the IVC wall. Average filter tilt from the Z‐axis was 19 degrees (range 8–56). Filters observed in the case study were either Bard G2X (n = 6) or Cook Celect (n = 7). Average filter dwell time was 421 days (range 47–1053). There were no major complications observed. Conclusion The rigid forceps technique can be readily emulated and is a safe and effective technique to remove severely tilted and embedded IVC filters. The development of this technique across both institutions has increased the successful filter removal rate, with perceived benefits to the safety profile of our IVC filter programme.